Developing a system for down-hole seismic testing together with the CPTU - Vitali, O. P M; Pedrini, R. A A [UNESP]; Oliveira, L. P R; Giacheti, H. L. [UNESP] (My University, 2012)
This paper presents a system for performing down-hole seismic test together with the piezocone test in order to determine the shear wave velocity (Vs) and for calculating the maximum shear modulus (Go); a basic parameter for analyzing the dynamic soil behavior and a reference value of the soil stiffness. The system components are described and tests results for checking the geophone response are also presented, both before and after installation into the probe. The system was used in down-hole tests carried out at three experimental research sites located in the interior of Sao Paulo State, Brazil, where in situ seismic test results are available. The Vs values measured in down-hole tests carried out with this system were consistent with those determined in cross-hole tests and with a commercial seismic piezocone, which enabled to validate the developed system.
Keywords: CPTU; Down-hole; Maximum shear modulus; Site investigation; Basic parameters; Crosshole tests; Experimental research; In-situ; Piezocone; Piezocone test; Reference values; Sao Paulo; Seismic test; Seismic testing; Shear wave velocity; Site investigations; Soil behaviors; Soil stiffness; System components; Elastic moduli; Seismology